PERAN MODERASI TEKNOLOGI PADA PENGARUH STRATEGI DIGITALISASI TERHADAP PENGEMBANGAN UMKM - Palebangan, Joan Gabriella; Mahfud, Mahfud; Iskandar, Zhamzam Nuraimah; Sabir, Firnawati; Arismunandar, Andi Patotori (Journal of Institution and Sharia Finance, 2024)
This research aims to determine the influence of digitalization strategies on the development of MSMEs which are moderated by technology. This research uses quantitative research with an accident sampling technique where the selection is made by chance. Data were analyzed using the Structural Equation Model Partial Least Square (SEM PLS) method. The research results show that the Digitalization Strategy and Digitalization Strategy for the Development of MSMEs Moderated by Technology have a positive influence on the development of MSMEs. However, technological moderation shows that there is no influence on the development of MSMEs.